Association between milk yield and serial locomotion score assessments in UK dairy cows - Archer, Simon C.; Green, Martin J.; Huxley, Jonathan (American Dairy Science Association, 2010)
This study investigated the effect of lameness, measured by serial locomotion scoring over a 12-mo period, on the milk yield of UK dairy cows. The data set consisted of 11,735 records of test-day yield and locomotion scores collected monthly from 1,400 cows kept on 7 farms. The data were analyzed in a multilevel linear regression model to account for the correlation of repeated measures of milk yield within cow. Factors affecting milk yield included farm of origin, stage of lactation, parity, season, and whether cows were ever lame or ever severely lame during the study period. Cows that had been severely lame 4, 6, and 8 mo previously gave 0.51 kg/d, 0.66 kg/d, and 1.55 kg/d less milk, respectively. A severe case of lameness in the first month of lactation reduced 305-d milk yield by 350 kg; this loss may be avoidable by prompt, effective treatment. Larger reductions can be expected when cases persist or recur. Evidence-based control plans are needed to reduce the incidence and prevalence of lameness in high yielding cows to improve welfare and productivity.